Models of Aire-Dependent Gene Regulation for Thymic Negative Selection - Danso-Abeam, Dina; Humblet-Baron, Stephanie; Dooley, James; Liston, Adrian (Frontiers in Immunology, 2011)
Mutations in the Autoimmune Regulator (AIRE) gene lead to Autoimmune Polyendocrinopathy Syndrome type 1 (APS1), characterized by the development of multi-organ autoimmune damage. The mechanism by which defects in AIRE result in autoimmunity has been the subject of intense scrutiny. At the cellular level, the working model explains most of the clinical and immunological characteristics of APS1, with AIRE driving the expression of tissue restricted antigens (TRAs) in the epithelial cells of the thymic medulla. This TRA expression results in effective negative selection of TRA-reactive thymocytes, preventing autoimmune disease. At the molecular level, the mechanism by which AIRE initiates TRA expression in the thymic medulla remains unclear. Multiple different models for the molecular mechanism have been proposed, ranging from classical transcriptional activity, to random induction of gene expression, to epigenetic tag recognition effect, to altered cell biology. In this review, we evaluate each of these models and discuss their relative strengths and weaknesses.